Empowering Marginalized Families through Client-Centered Counseling: A Sakinah Family Approach in Kampung Topeng, Malang - Rafiqah; Tristiadi Ardi Ardani; Sutrisno; Supriadi; Hosaini; Zohaib Hassan Sain; Lulu Maknunah (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2026)
This community service program aims to increase the understanding of the people of Kampung Topeng, Malang, about the concept of a harmonious family through a client-centered counseling approach combined with Islamic family values. The methodology used was a Community-Based Participatory Research (CBPR) approach involving 33 residents, community leaders, teachers, and village officials. The intervention involved three client-centered counseling modules tailored for children and adolescents, mothers, and fathers, supported by psycho-religious education, focus group discussions, panel discussions, community competitions, and collaborative reflection. The results show that the program enhanced participants' understanding of the values ​​of love, togetherness, and responsibility within the family. Furthermore, communication and empathy skills among family members showed positive development. Program outputs included training modules and a guidebook on harmonious families. It is therefore recommended that client-centered counseling integrated with Islamic family values ​​and accompanied by ongoing mentoring be adopted to strengthen family resilience in marginalized urban communities.